Data associated with "Analysis of acoustic Doppler current profiler mean velocity measurements in shallow flows" - Klema, Matthew R.; Pirzado, Abdul G.; Venayagamoorthy, S. Karan; Gates, Timothy K. (Colorado State University. Libraries, 2019)
Acoustic Doppler current profilers (ADCPs) are commonly used instruments for measurement of natural streamflow and flow in manmade channels. Velocities measured in a profile by the instrument are used to estimate the discharge in a channel. A Teledyne RD Instruments StreamPro ADCP was used to measure the mean velocity simultaneously with a laser Doppler anemometer(LDA) in a laboratory flume. An average of 3.9% under-prediction of the mean velocity measured by the ADCP occurred when compared to the measurements of the LDA. The sampling duration of the measurements was also found to impact the mean point velocities measured by up to 50%.
There are a total of 25 tab delimited text files that contain the data presented in the figures of the journal article, 'Analysis of Acoustic Doppler Current Profiler Mean Velocity Measurements In Shallow Flows'. In most cases all of the data is organized into text files named by plot and subplot. All text files for Figure 4 are broken into an individual text file for each data set. All data represents processed/analyzed data that was derived from the collected data by the instruments.
Department of Civil and Environmental Engineering
Keywords: acoustic doppler current profiler (ADCP); streamflow; flow measurement; uncertainty analysis